The relationship between parent-child attachment and fertility intention: the mediating role of family resilience and the moderating role of gender moderating - Li, Gui-Ying; You, Zhi-Qi; Yang, Guang-Hui (Frontiers in Psychology, 2025)
ObjectiveThe study aims to explore how parent-child attachment relates to college students fertility intention, mediated by family resilience and moderated by gender .MethodsA study surveyed 2186 college students using various scales to assess parent-child attachment, family resilience, fertility intention. Data analysis included descriptive stats, partial correlations, mediation and moderation effects.Results(1) Parent-child attachment (including its sub-dimensions: father attachment and mother attachment), family resilience (including its sub-dimensions: family beliefs and family strength), and fertility intention show significant positive correlations; (2) Total scores of parent- child attachment and family resilience positively predict fertility intention– Specifically, father attachment (rather than mother attachment) and family beliefs (rather than family strength) positively predict fertility intention; (3) After controlling for variables such as family economic status, family beliefs partially mediate the relationship between father attachment and future fertility intention; (4) Both segments of the mediating pathway are significantly moderated by gender– Male’s father attachment has a stronger promoting effect on family beliefs than female’s, male’s family beliefs directly drive fertility intention, while female’s family beliefs do not directly influence fertility intention.ConclusionThis study clarified the core role path of ‘father attachment → family beliefs → fertility intentions,’ and found that men are more likely to form family beliefs through father attachment, which can directly drive their fertility intentions, while women’s fertility intentions need to be improved by alleviating actual fertility costs. This result not only provides new evidence for the theoretical mechanism of ‘ parent-child relationships affecting fertility intentions,’ but also offers practical basis for formulating fertility intention enhancement strategies differentiated by gender and dimension.